Radiological assessment of extracranial vertebral artery variations: a computed tomography angiography study - Hajri, Faiza Al (2023)
We evaluated the incidence of intraforaminal and extraforaminal variations of the vertebral artery (VA) in the Omani population using computed tomography angiography (CTA). CTA results of 579 consecutive Omani patients (1158 VAs) were reviewed retrospectively for the analysis of unusual entrance transverse foramen (UE-V2), midline migration (MM), persistent first intersegmental artery (PFIA), and paracondylar process (PP) variations of VA. The anomalous origin and VA dominance were also determined. The sex and side differences in the incidence of these variations were analyzed using the Chi-square test. The incidence of UE-V2 was observed in 10.44% (121 out of 1158) of cases. The incidence of UE-V2 at different vertebral levels was observed in the sequence of C5 (71%) > C4 (20.7%) > C7 (7.43%) > C3 (0.8%). The incidence of MM variation was 1.29%. PFIA and PP variations were found in 0.17% and 0.60% of cases, respectively. Left-dominant VA was identified in 44.7% (259 out of 579) of subjects. The incidence of VA variations was not significantly associated with either sex or side. Anomalous VA origin from arch aorta (3.5%) and right common carotid artery (CCA) (0.08%) was identified. The incidence of UE-V2 in Omani subjects is comparatively higher than that reported in other Asian populations. A rare case of VA originating from the right CCA was also identified.